Design and Construction of Web-Based Social Assistance Fund Receipt Information System in Depok Village - Syari, Elfina (ENCRYPTION: Journal of Information And Technology, 2023)
The social assistance fund receipt system is a system that aims to record and manage social assistance funds quickly and transparently. In RT 001 / RW 003, Depok Village, there are obstacles in the management of social assistance funds that cause the process of receiving social assistance funds to be ineffective. Therefore, a web-based information system design is needed to minimize problems in the process. The purpose of writing is to find out the social assistance fund receipt system that is running in RT 001 / RW 003, Depok Village with the method used in writing this report is through literature studies and direct observation field studies to the place that is the object of writing. The results of observations obtained by the Author in the social assistance fund receipt system include managing social assistance funds, inputting data on recipients of social assistance funds and reports on recipients of social assistance funds.